2011
DOI: 10.1002/bem.20644
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of occupational exposure to extremely low frequency magnetic fields in hospital personnel

Abstract: It has been proposed that chronic exposure to extremely low frequency (ELF) magnetic fields (MF) in occupational environments could represent a risk factor for a number of disorders. Medical and technical workers in hospitals have been reported to be exposed to relatively strong ELF fields. The present work aims to characterize exposure to MF in the 5 Hz to 2 kHz frequency range in a large hospital through both instantaneous environmental measurements and personal monitoring of workers. The study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…Ubeda et al . reported that the mean exposure levels obtained from spot measurements ranged from a minimum of 0.03 ± 0.01 μT in nurses to a maximum of 0.39 ± 0.13 μT in physiotherapists in a study that also included surgeons, physicians, and radiologists . Our previous study reported that the mean ELF‐MF exposure of endodontic personnel during working hours was 0.03 ± 0.04 μT .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Ubeda et al . reported that the mean exposure levels obtained from spot measurements ranged from a minimum of 0.03 ± 0.01 μT in nurses to a maximum of 0.39 ± 0.13 μT in physiotherapists in a study that also included surgeons, physicians, and radiologists . Our previous study reported that the mean ELF‐MF exposure of endodontic personnel during working hours was 0.03 ± 0.04 μT .…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, the patients' mean ELF‐MF exposure levels were no different between the laparoscopic and robotic surgeries and were approximately same as the mean ELF‐MF exposure level of 0.11 μT in homes in North America . Previous studies reported a mean strength of ELF‐MFs ranging from 0.03 μT to 0.58 μT in various hospital locations .…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 shows the mean MF exposure levels of medical workers according to other studies (Roh et al. 2009, Úbeda et al. 2011) as well as those of the endodontic trainee and hygienists measured in this study.…”
Section: Resultsmentioning
confidence: 94%
“…2009). The averages of exposure levels obtained from spot measurements ranged from 0.03 ± 0.01 μT (minimum) in nurses to 0.39 ± 0.13 μT (maximum) in physiotherapists in a study that also included surgeons, physicians and radiologists (Úbeda et al. 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Another factor to be considered is the environment: areas where the general public and hospital personnel are exposed have to be selected. Some authors analyzed the exposure of healthcare workers to low-frequency radiation [8][9][10] . In our case, we are aiming at highfrequency radiation, so their results in terms of the more exposed areas are not directly applicable.…”
Section: Methodsmentioning
confidence: 99%